The Influence of Promotional Mix on Muslim Fashion Brand Towads Consumer Buying Decisions: Case of L.tru (Journal of Business and Management, 2021)
As a country with the largest muslim population in the world, The development of Muslim fashion in Indonesia has increased tremendously in the last few years. This is an excellent opportunity for businesses engaged in the fashion industry, yet it has become more difficult and challenging for businesses to compete. L.tru is one of the pioneers of muslim fashion industry in Indonesia that has been running for 15 years. In order to compete and achieve the company's sales target, L.tru implements the promotional mix that consists of advertising, sales promotion, personal selling, public relation, and direct marketing. This research aims to identify the influence of each element of promotional mix on consumer buying decisions in L.tru and give recommendations that can be implemented by L.tru. The data was collected by spreading the questionnaire and analyzed by PLS-SEM. The result shows that sales promotion, direct marketing, and public relations are significantly affecting consumer buying decisions and advertising has a positive but not significant influence on consumer buying decisions. On the other hand, personal selling has no influence on consumer buying decisions in L.tru.Keywords: Promotion mix, advertising, sales promotion, personal selling, public relations, direct marketing, consumer buying decisions